Evidences of fishing impact on the coastal gorgonian forests inside the Portofino MPA (NW Mediterranean Sea). (1st April 2020) - Betti, F.; Bavestrello, G.; Bo, M.; Ravanetti, G.; Enrichetti, F.; Coppari, M.; Cappanera, V.; Venturini, S.; Cattaneo-Vietti, R.
Abstract: The gorgonians Paramuricea clavata (Risso, 1826) and Eunicella cavolini (Koch, 1887) are important habitat-forming species within the Mediterranean coralligenous habitats, creating complex, three-dimensional forests that greatly contribute to the underwater landscape of the coastal hard grounds. Dense forests of both species are present within the Portofino Marine Protected Area (Ligurian Sea, NW Mediterranean Sea), showing a distinct bathymetric separation and site-specific differences. Quantitative evidences obtained with a monitoring census conducted in 2016 in 16 sites within the MPA support the existence of a widespread damage on these populations partially due to the mechanical injuries inflicted by recreational and professional demersal fishing gears. Considering all the studied populations, it resulted that 53% of the colonies of P. clavata and 36% of the colonies of E. cavolini were showing traces of impact, of which 10% in P. clavata and 7% in E. cavolini were due to direct entanglements with lost longlines. In the last decades, recurrent massive mortalities related to temperature anomalies and storms, have greatly reduced the gorgonian populations in this area and fishing impact severely affects survived or recovering colonies. Considering the vulnerable status of these species, and the increasing stress due to climate change, a correct management of the anthropic pressures is strongly needed to help preserving these relevant ecosystems. Graphical abstract: Image 1 Highlights: - Paramuricea clavata and Eunicella cavolini are important ecosystem-engineers. -Dense forests of these species thrive inside the Portofino MPA (NW Mediterranean). -51% of P. clavata and 36% of E. cavolini colonies were impacted by fishing gears. -The density of impacted colonies was strongly related to the fishing effort in the area. -A management of fishing pressures is needed to preserve these relevant ecosystems.